2007
DOI: 10.1111/j.1365-2672.2007.03295.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of intestinal bacteria in the Chinese mitten crab (Eriocheir sinensis)

Abstract: Aims:  To identify the dominant intestinal bacteria in the Chinese mitten crab, and to investigate the differences in the intestinal bacteria between pond‐raised and wild crabs. Methods and Results:  The diversity of intestinal bacteria in the Chinese mitten crabs was investigated by denaturing gradient gel electrophoresis (DGGE) fingerprinting, 16S rRNA gene clone library analysis and real‐time quantitative PCR. The principal component analysis of DGGE profiles indicated that substantial intersubject variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 31 publications
4
48
1
Order By: Relevance
“…Though DGGE has some drawbacks, like PCR biases, heteroduplex formation and comigration of bands, for comparison of spatial and temporal variation of diversity it can be coupled to statistical tools like Diversity indices, Principal Coordinate Analysis, Principal Component Analysis and Correspondence Analysis. Using these statistical tools, one can compare the microbial diversity among the sampling sites or variation of diversity with respect to changes in environmental parameters (Desnues et al 2007;Li et al 2007;Webster et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Though DGGE has some drawbacks, like PCR biases, heteroduplex formation and comigration of bands, for comparison of spatial and temporal variation of diversity it can be coupled to statistical tools like Diversity indices, Principal Coordinate Analysis, Principal Component Analysis and Correspondence Analysis. Using these statistical tools, one can compare the microbial diversity among the sampling sites or variation of diversity with respect to changes in environmental parameters (Desnues et al 2007;Li et al 2007;Webster et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to nutrition and digestion, the immanent microbiota play crucial roles in the immune response of their animal hosts (Cheung et al, 2015), and an imbalance of host–microbiota homeostasis has been shown to be responsible for certain illnesses (Chen et al, 2015). A previous study has reported symbiotic bacteria in crabs to belong to the phyla Bacteroidetes, Proteobacteria, Firmicutes, and Tenericutes (Li et al, 2007; Givens et al, 2013; Chen et al, 2015; Zhang et al, 2016). Of these symbiotic bacteria, Tenericutes are unique, because they lack a cell wall, are small in size, and possess a reduced genome (Ryan and Ray, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a similar phenomenon has been reported in studies of the gut microbiota of the Chinese mitten crab Eriocheir sinensis (Li et al 2007;Chen et al 2015). Species of Mycoplasmataceae found in the gut content of E. sinensis from Lake Tai (Chen et al 2015) were absent in individuals from the Yangtze River estuary and Chongming Islands (Li et al 2007). More studies will be needed to determine the relationships between Mycoplasmataceae and X. testudinatus.…”
Section: Composition Of Eukaryotes and Prokaryotes In Xenograpsus Tesmentioning
confidence: 65%
“…This may be due to an insufficient sequencing throughput for these samples since the Good's coverage of the 16S rDNA library was <0.8 for the vent crabs, and the ratio of detected OTUs/estimated OTUs by Chao1 was <0.3. Indeed, a similar phenomenon has been reported in studies of the gut microbiota of the Chinese mitten crab Eriocheir sinensis (Li et al 2007;Chen et al 2015). Species of Mycoplasmataceae found in the gut content of E. sinensis from Lake Tai (Chen et al 2015) were absent in individuals from the Yangtze River estuary and Chongming Islands (Li et al 2007).…”
Section: Composition Of Eukaryotes and Prokaryotes In Xenograpsus Tesmentioning
confidence: 71%
See 1 more Smart Citation